First record of cestode Mathevotaenia erinacei Meggitt, 1920 from Hedgehog Hemiechinus auritus in Basrah Province, Iraq - J.K. AL-Zihiry, Khalid (University of Thi-Qar Journal of Science, 2009)
The present study was carried out on 35 specimens of long eared hedgehog Hemiechinus auritus Gmelin,1770 in several localities of Abu Al-Khasib district, Basrah province during the period from March to September, 2004.The intestine of hedgehog was removed and examined to searching for helminth parasites. One species of cestode were collected from 4(11.4 %) of examined animals . The isolated cestode was similar to original description of Mathevotaenia erinacei, therefore redescription and Comparison between two measurements were given. The present finding of this cestode represent its first Record in iraq.